Analysing the impact of COVID-19 on over-the-top media platforms in India. Issue 5 (25th August 2020) - Madnani, Divya; Fernandes, Semila; Madnani, Nidhi
Abstract : Purpose: The outbreak of COVID-19 saw a robust increase in viewership of over-the-top (OTT) media platforms. This study aims to investigate the impact of COVID-19 on OTT platforms in India, as it has led to reshaping consumer content preferences. Design/methodology/approach: The authors have conducted primary research by doing a survey and focus group discussion. The first study has focused on the impact of various factors such as time, content, convenience, satisfaction and work from home (WFH) on OTT platforms during the COVID-19 crisis and the second study has focused on change in behavior of people before and during lockdown using visual representation. Findings: The findings of this study show that lockdown has played a major role in the increase in viewership of OTT platforms, as people working from home are also using OTT platforms more. The average hours spent on OTT have increased from 0–2 to 2–5 h and average spending that users are willing to make on OTT platforms is Rs 100–300 (per month). The satisfaction level of customers is directly related to space to watch with family, time to use OTT platforms, the quality of content on OTT platforms and preference of OTT platform over television. Also, factors such as age group, occupation, city and income groups also determine the usage of the OTT platform. Originality/value: The main contribution of this paper is to analyze the customer needs that impact their satisfaction level.